The creeping shadow - Stroud, Jonathan (Stroud, Jonathan. Lockwood & Co., 2016)
"A terrible crime forces Lockwood to turn to Lucy for help, setting them on the trail of dark secrets at the heart of London society. Both professionally and personally, their investigation stirs up forces they may not be able to control. . ."--